1998
DOI: 10.1108/00907329810307759
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Future: A Preliminary Study of the Process of How Undergraduate Students Evaluate Web Sources

Abstract: In this article, Scholz‐Crane examines current practices among students in an entry‐level composition class. Students used in this study were divided into two groups. Each group was asked to read two separate Web documents. One group was asked to evaluate each site based on criteria supplied by Scholz‐Crane and then to comment on their overall conclusions about the validity of each site. The second group were asked to write essays detailing the criteria they would use to evaluate each Web site and then to draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Indeed, studies have found that users are seldom diligent in checking the accuracy of the information they obtain online (Flanagin & Metzger, 2000;Scholz-Crane, 1998). In a series of studies, Metzger and Flanagin examined the degree to which Internet consumers use each of the recommended criteria (i.e., accuracy, authority, objectivity, currency, and coverage) to gauge the credibility of the information they found online.…”
Section: Checklist Approachesmentioning
confidence: 98%
See 3 more Smart Citations
“…Indeed, studies have found that users are seldom diligent in checking the accuracy of the information they obtain online (Flanagin & Metzger, 2000;Scholz-Crane, 1998). In a series of studies, Metzger and Flanagin examined the degree to which Internet consumers use each of the recommended criteria (i.e., accuracy, authority, objectivity, currency, and coverage) to gauge the credibility of the information they found online.…”
Section: Checklist Approachesmentioning
confidence: 98%
“…Based on that, the literature identifies five criteria that users should employ in their assessments of the credibility of Internet-based information: accuracy, authority, objectivity, currency, and coverage or scope (see Alexander & Tate, 1999;Brandt, 1996;Fritch & Cromwell, 2001;Kapoun, 1998;Meola, 2004;Scholz-Crane, 1998;Smith, 1997).…”
Section: Critical Evaluation Skills: Training Users To Evaluate Onlinmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing criteria from both groups to standard evaluation criteria, she found that a checklist alone was insuffi cient to help students evaluate Web sites and, further, that students needed help in identifying components or elements of Web documents. 7 In an effort to increase effective use of the Internet for research, Anne F. Pierce used pre-and posttest scores to compare the performances of high school students. She found that, despite their high opin ions of their own abilities, students were quite unskilled in research techniques that effectively used Internet resources.…”
Section: Literature Reviewmentioning
confidence: 99%